2021
DOI: 10.1021/acssynbio.1c00136
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Cell-Free Composition Controls the Time Delay, Dynamics, and Productivity of TX-TL Expression

Abstract: The composition of cell-free expression systems (TX-TL) is adjusted by adding macromolecular crowding agents and salts. However, the effects of these cosolutes on the dynamics of individual gene expression processes have not been quantified. Here, we carry out kinetic mRNA and protein level measurements on libraries of genetic constructs using the common cosolutes PEG-8000, Ficoll-400, and magnesium glutamate. By combining these measurements with biophysical modeling, we show that cosolutes have differing effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…This enhanced performance suggested that protein synthesis was quite rapid as well. It has been reported that viscosity (crowding effect) of the cell-free system can have a significant effect in their function, affecting transcription and translation rate efficiency . However, addition of just QDs whose surface was blocked with assembly of a non-specific protein and lacking sensors did not have any overt crowding effect on this presumably due to their relatively low overall concentration (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…This enhanced performance suggested that protein synthesis was quite rapid as well. It has been reported that viscosity (crowding effect) of the cell-free system can have a significant effect in their function, affecting transcription and translation rate efficiency . However, addition of just QDs whose surface was blocked with assembly of a non-specific protein and lacking sensors did not have any overt crowding effect on this presumably due to their relatively low overall concentration (data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…This could result in differential transcription kinetics, RNA stability, or other factors related to our observation of MGA expression, which emphasizes the importance of chassis strain selection for the desired cell-free application. , The RNase E truncation product also decreases in abundance after runoff, which may further reduce the activity of this enzyme (Data Set S2). However, translational limitation during CFE from both viral and endogenous promoters is supported by several studies that incorporated ribosome profiling, LC–MS, , and quantitative modeling. …”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of high concentrations of acetate or glutamate anions in the wash buffer during cell harvesting does impact the underlying metabolome of resulting cell extracts and could alter the proteome and observed gene expression activity through regulatory changes that occur prior to cell lysis, particularly during the runoff incubation. , Concentrations of CFE reagents and their byproducts must also be considered and optimized for different applications . For example, including polyamines (such as putrescine) and crowding reagents (such as polyethylene glycol and Ficoll) can improve CFE through nucleic interactions and/or molecular crowding effects, but these components can reduce protein synthesis above an optimal concentration. ,, In addition to these insights, the metabolomics data enable inferences into related compounds that could not be detected on this specific analytic pipeline, such as some phosphorylated metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to key-lock type specific interactions, environmental parameters in the cytoplasm have a substantial effect on gene expression activity. For example, macromolecular crowding causes either the promotion or repression of both TX and TL in vitro experiments using cell lysates [ 25 , 26 , 27 ]. Using these cell-free gene expression systems, we found that polyamine, with a trivalent positive charge (3+), completely inhibits protein synthesis above a certain threshold concentration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%